How Do Firms Respond to State Retirement Plan Mandates? - Bloomfield, Adam,Lee, Kyung Min,Philbrick, Jay,Slavov, Sita N. (National Bureau of Economic Research, 2023)
This paper investigates the effect of state retirement plan mandates on the supply of employer-sponsored retirement plans (ESRPs) by firms. These policies require employers to either (1) offer ESRPs to workers or (2) facilitate automatic payroll deductions that are deposited into individual retirement accounts (IRAs) established for workers by the state. In this paper, we utilize individual-level data from the Current Population Survey (CPS) and firm-level data from Form 5500 filings to examine the effect of these automatic-enrollment IRA (
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Rentenpolitik; Betriebliche Altersversorgung; Wirkungsanalyse; USA; Household Saving; Personal Finance; State and Local Government: Health; Education; Welfare; Public Pensions; Retirement; Retirement Policies